Educational needs of adult learners at Xihoko Public Adult Learning Centre in Limpopo Province of South Africa - Mathye, Vonani Ronnel (My University, 2015)
This study describes the research carried out in the Limpopo Province of South Africa, with Xihoko Public Adult Learning Centre as a site of the study. The aim of the study is to get insight into the educational needs of adult learners at Xihoko PALC. The study also intends to investigate the aims and objectives of the programmes offered at Xihoko PALC. In order to achieve the aims outlined above, I formulated the main research question of the study as follows:  What are the educational needs of adult learners at Xihoko Public Adult Learning Centre? In trying to answer the question outlined above, I decided to undertake an explorative study in order to investigate the educational needs of adult learners at Xihoko PALC in Limpopo Province of South Africa. In Chapter 1, I gave a description of South Africa in the apartheid era and post apartheid era in terms of its geographical setup and education. The aims and objectives of this study and the research questions are indicated. The scope of the study is explained. It was the objective of this study to contribute towards identifying educational needs of adult learners at Xihoko PALC in Limpopo Province of South Africa, and to ensure that the educational needs of adult learners are addressed by the programmes offered. In Chapter 2, the theoretical framework of the study of the educational needs of adult learners at Xihoko PALC in Limpopo Province is indicated. Based on reading of the relevant literature and preliminary discussions with experts in the field of adult education, it appeared that factors such as: agricultural, computer and sewing skills as well as basic literacy and numeracy are possible educational needs of adult learners at Xihoko PALC. Key concepts are defined in this chapter. ii In Chapter 3, I describe the design of the study. The main focus of this chapter was to discuss the path of data collection. An explanation and discussion of the instruments that were utilised to collect data from different stakeholders in various phases of data collection is also given. I further explain how the data that was collected from various phases was analysed using qualitative data analysis methods. The chapter concludes by discussing the ethical considerations of the study. Chapter 4 presents the findings of the study according to the views and perceptions of the interviewees. This section prepared the study for the next stage of the investigation where I established whether or not the findings provide answers to the research question. In this chapter, I also presented an overview of Xihoko PALC. A description of the programmes which are offered at Xihoko PALC is given. I also indicated the aims and objectives of Xihoko PALC. The chapter further discusses issues around educators and the characteristics of adult learners at Xihoko PALC. I have also outlined in detail the views of the interviewees in relation to the critical factors of this study. The chapter concludes by discussing the findings of observations based on Xihoko PALC. Chapter 5 presents the final conclusion and recommendations of the study. Conclusions were made based on the findings of the investigation. The chapter integrates the information from previous chapters in discussing the educational needs of adult learners at Xihoko PALC in the Limpopo Province. It also provides suggestions which might contribute towards addressing the educational needs of adult learners. Recommendations for further study have been outlined. The chapter concludes by discussing what I call ‘reflections’, a section that was about my main learning areas and the limitations that I encountered during the process of this research.
Thesis (M. A. Education (Adult Education)) -- University of Limpopo, 2015
Keywords: Adult education; Adult learners; Educational needs; Adult education -- South Africa -- Limpopo; Education -- South Africa -- Limpopo; Continuing education